PEMBUKTIAN PERJANJIAN LISAN DALAM SENGKETA HUTANG PIUTANG: STUDI PUTUSAN PN BALIKPAPAN NO. 146/PDT.G/2021 - Akbar Wahyu Purnawan; Miko Aditiya Suharto (Universitas Labuhanbatu, 2025)
Oral agreements are still commonly used in civil law practice, particularly in legal relationships based on mutual trust. This study examines the evidentiary strength of oral debt agreements through an analysis of Decision Number 146/Pdt.G/2021/PN BPP. The research employs a normative juridical method using statutory, case, and conceptual approaches. Research data were obtained through library research on primary legal materials, including the Indonesian Civil Code and relevant court decisions, as well as secondary legal materials in the form of books and scholarly journal articles. The findings indicate that oral agreements are legally recognized as long as they fulfill the validity requirements of contracts as stipulated in Article 1320 of the Indonesian Civil Code. In the case examined, the Panel of Judges established the existence of a legal relationship between the creditor and the debtor based on evidence such as fund transfer records, correspondence, and witness testimony, thereby confirming that the oral agreement possessed sufficient evidentiary value. However, the request for the seizure of shares as security was rejected because it conflicted with Supreme Court guidelines and involved public interests in the electricity sector. This study has both theoretical and practical significance, as it clarifies the legal standing of oral agreements in civil evidentiary law and provides guidance for judges and litigants in assessing evidence in debt-related disputes. Nevertheless, the study recommends that agreements be documented in written form to ensure legal certainty and facilitate proof in judicial proceedings. Keywords: oral agreement; evidence; debt; breach of contract